Mortality of serious diabetic complications is not predictable by heat shock protein-70 in emergency department: a prospective pilot study - İsmail Borazan; Gülşen Akçay; Bedriye Müge Sönmez; Murat Özdemir; Arzu Kösem; Atakan Öztürk (The Egyptian Journal of Internal Medicine)
Abstract Background Heat Shock Protein 70 (HSP-70) is an intracellular expressed molecule induced by stress conditions such as Diabetic ketoacidosis (DKA) and Hyperosmolar hyperglycemic state (HHS), which are life-threatening complications of diabetes mellitus. This study aims to determine the prognostic utility of HSP-70 in DKA and HHS patients presenting to the emergency department (ED). Methods A prospective cross-sectional study was conducted on 45 diabetic patients aged over 18 years who attended the ED with DKA and HHS. The HSP-70 levels in the serum samples were determined using an enzyme-linked immunosorbent assay (ELISA) kit. Groups were compared in terms of mortality according to HSP-70 levels. Results The HHS group had a lower HSP-70 level, but there was no statistical significance between the DKA and HHS groups. The overall mortality rate was 26.6%. The HSP-70 levels of the deceased patients were lower than those of the discharged ones. HSP-70 levels were lower in the deceased patients in the DKA group and higher in the deceased patients in the HHS group, but there was no statistical significance. Conclusion There was no direct relationship between the HSP-70 levels and mortality among patients with DKA and HHS in ED.